2012
DOI: 10.1038/onc.2012.279
|View full text |Cite
|
Sign up to set email alerts
|

Role of AMPK in UVB-induced DNA damage repair and growth control

Abstract: Skin cancer is the most common cancer in the U.S., while DNA-damaging UVB radiation from the sun remains the major environmental risk factor. Reducing skin cancer incidence is becoming an urgent issue. The energy-sensing enzyme 5’-AMP-activated protein kinase (AMPK) plays a key role in the regulation of cellular lipid and protein metabolism in response to stimuli such as exercise and changes in fuel availability. However, the role AMPK in the response of skin cells to UVB damage and in skin cancer prevention r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(108 citation statements)
references
References 46 publications
4
101
0
3
Order By: Relevance
“…Frozen tissues were obtained under consent at the Section of Dermatology, Department of Medicine, University of Chicago as in our previous studies (46). …”
Section: Methodsmentioning
confidence: 99%
“…Frozen tissues were obtained under consent at the Section of Dermatology, Department of Medicine, University of Chicago as in our previous studies (46). …”
Section: Methodsmentioning
confidence: 99%
“…In Vitro Cell Proliferation Assay-Cell proliferation of A431 and A375 stable cells was analyzed using the MTS assay (Promega, Madison, WI) according to the manufacturer's instructions as in our recent studies (21). The BrdU assay was monitored using a cell proliferation ELISA BrdU (colorimetric, Roche Applied Science) kit according to the manufacturer's instructions as in our previous studies (26).…”
Section: Methodsmentioning
confidence: 99%
“…Emerging data indicate that AMPK plays an important role in tumor suppression [24, 25]. It was recently reported that AMPK regulates UVB-induced DNA damage repair in skin tumor cells [26], as well as playing a role in NHEJ via the LKB1-AMPK signaling pathway [27]. However, the exact role of the two AMPKα isoforms and the mechanism by which AMPK might control the cell cycle and DNA damage remain elusive.…”
Section: Introductionmentioning
confidence: 99%